2019
DOI: 10.1097/coc.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation in Stereotactic Body Radiation Therapy for Pancreatic Cancer

Abstract: SBRT for pancreatic cancer results in LC rates of 60% to 83% and clinically significant toxicity of <7%. Increasing BED10 beyond 70 Gy was not associated with increased rates of 1-year LC or acute toxicity. Increasing BED3 beyond 100 Gy was not associated with increased rates of late toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
0
36
1
Order By: Relevance
“…10,11,14 The median OS and 2-year OS rates in our study were in line with the ones in Krishnan et al 14 (median OS: 20.3 months versus 17.8 months, 2-year OS rate: 36.8% versus 36.0%, 3-year OS rate: 18.7% versus 31.0%). However, there were controversial results from the meta-analysis; 34 the median OS of two studies with the most weight employing BED 10 >70 Gy was 12.5 months and 10.3 months, which was inferior to our study. In contrast, the median OS with the most weight employing a BED 10 of 60-70 Gy from two studies were found to be 13.9 months and 15.0 months, respectively.…”
Section: Discussioncontrasting
confidence: 95%
“…10,11,14 The median OS and 2-year OS rates in our study were in line with the ones in Krishnan et al 14 (median OS: 20.3 months versus 17.8 months, 2-year OS rate: 36.8% versus 36.0%, 3-year OS rate: 18.7% versus 31.0%). However, there were controversial results from the meta-analysis; 34 the median OS of two studies with the most weight employing BED 10 >70 Gy was 12.5 months and 10.3 months, which was inferior to our study. In contrast, the median OS with the most weight employing a BED 10 of 60-70 Gy from two studies were found to be 13.9 months and 15.0 months, respectively.…”
Section: Discussioncontrasting
confidence: 95%
“…In the abovementioned systematic review, the authors report that total SBRT dose and a higher number of fractions were significantly associated with local control at one year, but further details were lacking [8]. Another meta-analysis dedicated to the topic of radiation dose-escalation for pancreatic cancer by Zaorsky et al has recently been published [9]. This review included the results of SBRT for non-metastatic pancreatic cancer in 508 patients within a total of 15 studies.…”
Section: Biological Dose Escalation For Pancreatic Cancermentioning
confidence: 99%
“…The median OS and 2-year OS rates of patients with BED 10 > 70Gy in our center (data not published) were consistent with the ones in Krishnan et al [27] (median OS: 20.3 months vs. 17.8 months, 2-year OS rate: 36.8% vs. 36.0%, 3-year OS rate: 18.7% vs. 31.0%). However, there were controversial results from the meta-analysis [28]. The median OS of two included studies with the most weight employing BED 10 > 70Gy was 12.5 months and 10.3 months, while the median OS with the most weight employing a BED 10 of 60-70Gy from another two studies were found to be 13.9 months and 15.0 months, respectively.…”
Section: Discussionmentioning
confidence: 97%